Background and Students' Perceptions of Science Classroom Learning Environment and Teacher Interpersonal Behaviour in Jammu, India. - Koul, Rekha; Fisher, Darrell (Kluwer Academic Publishers, 2005)
This article reports research into associations between students’ cultural background and their perceptions of their teacher’s interpersonal behaviour and classroom learning environment. A sample of 1021 students from 31 classes in seven co-educational private schools completed a survey including the Questionnaire on Teacher Interaction (QTI), the What Is Happening In this Class? (WIHIC) and a question relating to cultural background. Statistical analyses showed that the Kashmiri group of students perceived their classrooms and teacher interaction more positively than those from the other cultural groups identified in the study.